Association of Gene Polymorphisms in APOE and BIN1 With Dementia of Alzheimer's Type Susceptibility in Chinese Han Population - Li, Xiaoyue; Zhang, Yelei; Chen, Xinyu; Yuan, Hongwei; Wang, Zhiqiang; Wang, Guoqiang; Zhang, Kai; Liu, Huanzhong (Frontiers in Psychiatry, 2021)
Abstract: Objectives: Dementia of the Alzheimer's type (DAT) is the most common chronic neurodegenerative disease. At present, the pathogenesis of DAT is not completely clear, and there are no drugs that can cure the disease. Once an individual is diagnosed with DAT, the survival time is only 3 to 9 years. Therefore, there is an urgent need to determine the etiology of DAT and the associated influencing factors to find a breakthrough in the treatment of DAT. Methods: We studied the relationship between polymorphisms in several genes (including BIN1 and APOE) and DAT susceptibility and the effects of sex differences on DAT. Our study included 137 patients with DAT and 509 healthy controls (HCs). Results: The APOE rs429358 polymorphism CC and CT genotypes were associated with an increased risk of DAT in women. We found a significant association between APOE ε4 and DAT. The frequency of the ε4 allele in the DAT group (15.5%) was higher than that in the HC group (8.7%). The BIN1 rs7561528 polymorphism was associated with a decreased risk of DAT in men. Conclusions: APOE gene rs429358 and BIN1 gene 7561528 genes may affect the susceptibility to DAT in a Chinese Han population.